Nodular regenerative hyperplasia in patients with inflammatory bowel disease treated with azathioprine. Issue 10 (15th May 2007) - Vernier-Massouille, G; Cosnes, J; Lemann, M; Marteau, P; Reinisch, W; Laharie, D; Cadiot, G; Bouhnik, Y; De Vos, M; Boureille, A; Duclos, B; Seksik, P; et al.
Abstract : Aim: To assess the characteristics and clinical course of nodular regenerative hyperplasia (NRH) in patients with inflammatory bowel disease treated with azathioprine, so as to estimate the frequency of this complication and search for risk factors. Methods: Cases were identified through a systematic survey of patients followed at 11 centres. At one centre, the cumulative risk of NRH was estimated and a case–control study was undertaken to identify risk factors. Results: 37 cases of NRH (30 male, 7 female) were identified between 1994 and 2005. The median dose of azathioprine was 2 mg/kg/d (range 1.5 to 3.0). The median time between the start of azathioprine and the diagnosis of NRH was 48 months (range 6 to 187). After a median follow up period of 16 months (range 1 to 138), 14 patients developed complications of portal hypertension. Using multivariate analysis, male sex and stricturing behaviour were the two risk factors associated with NRH in patients treated with azathioprine. The cumulative risk calculated from the database (one centre) was 0.5% at 5 years (95% confidence interval, 0.11 to 0.89) and 1.25% at 10 years (0.29 to 2.21). Conclusions: NRH is a rare but potentially severe complication of azathioprine in patients with inflammatory bowel disease. Clinicians should be aware of this complication, and should monitor liver function tests and platelet counts closely in their patients.